The Confucius Institute and Chinese public diplomacy in Africa: A propaganda agency masquerading as an NGO? - (:unkn) unknown (My University, 2022)
The Confucius Institute and its centers of Chinese culture have always been considered essential for developing a favorable image of China in African countries. Although self-declared nonprofit, non-governmental organizations (NGOs), the Confucius Institute and its cultural centers disseminate ideas with the aim of seducing and influencing a target audience. Their aim is to promote China not only as a country of opportunity but also as a provider of opportunities abroad. In this context, Africa is a land ripe for experimentation, where China can impose its political agenda on international affairs and strengthen its international influence. This article will analyze to what extent the Confucius Institute acts as a Chinese-style NGO. It will also highlight the way in which this institution, qualified as “civil society” by Chinese political scientists within the Chinese Ministry of Foreign Affairs, is redefining and instrumentalizing corporate social/societal responsibility in support of Chinese public diplomacy in Africa in order to construct and defend the image of Beijing as a benefactor.
Keywords: African Research